2021
DOI: 10.3390/ijms222111439
|View full text |Cite
|
Sign up to set email alerts
|

From Primary MSC Culture of Adipose Tissue to Immortalized Cell Line Producing Cytokines for Potential Use in Regenerative Medicine Therapy or Immunotherapy

Abstract: For twenty-five years, attempts have been made to use MSCs in the treatment of various diseases due to their regenerative and immunomodulatory properties. However, the results are not satisfactory. Assuming that MSCs can be replaced in some therapies by the active factors they produce, the immortalized MSCs line was established from human adipose tissue (HATMSC1) to produce conditioned media and test its regenerative potential in vitro in terms of possible clinical application. The production of biologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…A growing amount of evidence suggests that MSCs primarily exert their in vivo effects through paracrine signaling, and the range of factors secreted by MSCs is highly adaptable. Previous research has demonstrated that the immortalization of MSCs can impact the spectrum of secreted proteins [33]. Consistent with our findings, Paprocka and colleagues have observed high levels of MCP-1 and GRO in immortalized cells.…”
Section: Discussionsupporting
confidence: 93%
“…A growing amount of evidence suggests that MSCs primarily exert their in vivo effects through paracrine signaling, and the range of factors secreted by MSCs is highly adaptable. Previous research has demonstrated that the immortalization of MSCs can impact the spectrum of secreted proteins [33]. Consistent with our findings, Paprocka and colleagues have observed high levels of MCP-1 and GRO in immortalized cells.…”
Section: Discussionsupporting
confidence: 93%
“…Also, many authors are evaluating the possibility of using immortalized cells in conditions where tumor growth is impossible. For example, in the production of an immortalized erythroid progenitor and platelet precursor, in which the final product is nuclear-free under ideal conditions when using filtration systems or other purification methods [ 54 , 55 , 56 , 57 , 59 , 60 ]; or using immortalized cells as producers of a conditioned medium with therapeutic properties, where there are no cells in the final product when also using filtration systems [ 89 , 90 , 91 , 93 , 94 ]; as well as using immortalized cells as a material for the manufacture of bioconstructions, in particular, a bioartificial kidney and a bioartificial liver, in some variants of the designs in which the cells are delimited from the body by membranes [ 106 , 122 , 123 ]. Therefore, the oncogenicity of immortalized cells is a serious problem that stands in the way of their application in medicine, so a thorough study of the oncogenic potential of candidate cells is necessary before moving on to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated the equally high regenerative potential of the conditioned medium obtained from these cells in an in vitro chronic wound model [ 93 ]. In a recent 2021 study, the same group of authors demonstrated that HATMSC line cells secrete more pro-regenerative factors than primary MSCs, and the regenerative efficiency of the supernatant of these cells in vitro was also demonstrated once more [ 94 ].…”
Section: Immortalized Cells As Producersmentioning
confidence: 99%
“…Moreover, immortalised cell lines offer a pure population of cells, which is necessary to deliver a consistent cell sample and reproducible results [ 15 ]. It is acknowledged that a steady, immortalised cell line that does not go through aging would be a successful producer of biologically active factors in indefinite quantities compared to primary cell lines, qualifying their use in stem cell therapy to be repeatable and enhanced considering the number of administrations [ 16 ]. Adipose-derived mesenchymal stem cells are capable of multi-differentiation into adipocytes, osteoblasts, chondrocytes, and smooth muscle cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%